2021
DOI: 10.2147/idr.s335103
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pathogens, Drug-Resistance Profile and Its Associated Factors from Patients with Suspected Peritonitis in Southern Ethiopia

Abstract: Background: Ascitic fluid plays a critical role in the microbiological diagnosis of peritonitis. Drug-resistant bacterial infection of the peritoneal cavity is becoming a public health threat. However, data on bacterial profile and antimicrobial-resistant pattern of isolates from the ascitic fluid are scarce. Thus, this study was aimed to assess drug-resistant bacteriological profiles and factors associated with peritonitis in southern Ethiopia. Methods: An institutional-based cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 23 publications
7
11
1
Order By: Relevance
“…Escherichia coli (35.8%) and Klebsiella spp (17.0%) were identi ed as the commonest bacteria cultured from infected peritoneal uid. These ndings are similar to the study done in Ethiopia by Alelign, (10) which reported E. coli (36.67%) and Klebsiella (20%) to be the commonest isolates. Furthermore, other studies conducted in Tanzania by Seni et (12); in Nigeria by Akujobi et al (25) and in India by Kumar-m al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Escherichia coli (35.8%) and Klebsiella spp (17.0%) were identi ed as the commonest bacteria cultured from infected peritoneal uid. These ndings are similar to the study done in Ethiopia by Alelign, (10) which reported E. coli (36.67%) and Klebsiella (20%) to be the commonest isolates. Furthermore, other studies conducted in Tanzania by Seni et (12); in Nigeria by Akujobi et al (25) and in India by Kumar-m al.…”
Section: Discussionsupporting
confidence: 91%
“…Following secondary peritonitis, different bacterial organisms may be involved mainly depending on the cause of the peritonitis. Drug-resistant to bacteria that cause infections of peritoneal cavity are becoming a public health concern (10). Although antimicrobial resistance containment interventions in healthcare structures have mostly been implemented in high-income countries, there is a pressing need to intervene in the antimicrobial resistance problem in low and middle income countries (LMIC) such as Uganda (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa isolates were resistant to tetracycline (91.7%), ampicillin (66.7), and cotrimoxazole (60.0%). Comparable findings were also reported elsewhere from Ethiopia [28,41,42]. In addition, that it had lower resistance to ciprofloxacin was in line with the literature evidences [26,43].…”
Section: The Antibiotic Resistance Of Bacterialsupporting
confidence: 91%
“…Its resistance to the tested antibiotics ranged from 15 to 86% with the overall rate of 55.7% which is lower than the report from Greek where it was 88% [27]. On the other hand, it was higher than the report of resistance, 40%, observed in patients with suspected peritonitis in Southern Ethiopia [28] and the 3 years retrospective study report from the same region in which the resistance of S. aureus was 42.02% [23] conducted elsewhere in Ethiopia and Nigeria [20,29]. The resistance towards ampicillin in this study was extremely higher than that reported for Enterococci elsewhere in Ethiopia [30].…”
Section: The Antibiotic Resistance Of Bacterialcontrasting
confidence: 57%